2018
DOI: 10.3233/bmr-171067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ankle taping on postural control measures during grasp and release task in patients with chronic ankle instability

Abstract: In CAI patients Mulligan ankle taping can improve postural control by decreasing velCOP, therefore Mulligan taping can have immediate positive effects on postural parameters and maintenance of dynamic postural control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Twenty-two preexperimental repeated-measures studies were found ( 12 , 26 , 34 , 35 , 37 , 38 , 39 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 57 , 58 ), two of which were also crossover ( 37 , 49 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-two preexperimental repeated-measures studies were found ( 12 , 26 , 34 , 35 , 37 , 38 , 39 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 57 , 58 ), two of which were also crossover ( 37 , 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…The interventions that addressed the effect of bandages on kinematics mainly used inelastic bandages ( 12 , 26 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 57 , 58 ), probably due to their lower capacity of deformation in relation to elastic bandages, which provide greater stability to the joint ( 63 ). Although in the analyzed studies inelastic bandages were the most used to modify the joint position of the ankle, both methods obtained positive results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equivocal evidence has been yielded by several studies that have examined the effects of KT on ankle joint stability in CAI patients [10,12,[15][16][17][18]. Some studies have found that KT potentially decreases postural sway, thus providing reinforcement of ankle stability during functional tasks, such as the Star Excursion Balance Test (SEBT) and Y balance test [10,19,20].…”
Section: Introductionmentioning
confidence: 99%